COVID-19 canceled Omed-omedan Festival 2020. Local Elders: The Rite Would be Carry On! - I Komang Bayu Segara (Bali Tourism Board, 2020)
The Government's decision to impose social restrictions threatened to cancel the Sesetan Heritage Omed-omedan Festival. Authority concerned that the crowd, both the Omed-omedan participants and spectators, might become a cluster for SARS-CoV-2 virus spread. However, to cancel the Omed-omedan might be challenging compared to cancel the Ogoh-ogoh parade on the night before Nyepi, Pengerupukan. Omed-omedan is a ritual in the Banjar Kaja Sesetan that is participated by local unmarried residents aged 17 to 30. It is a sacred tradition that should avoid being neglected. The ritual has been developed into an annual tourism event that attracts local and foreign visitors to witness the sheer and joyous festival. However, covid-19 pandemic threatened to cancel the Sesetan Heritage Omed-omedan Festival in 2020. after being discussed by the Sesetan village leaders, it was decided that the Omed-omedan would be held without any accompanying festival such as an entertainment stage, cultural parade, flea market or even grand opening ceremony to control the crowd. The participant of the Omed-omedan also reduced to only three pairs of adolescents, with strict health protocol. Nevertheless, traditional village leaders of Sesetan also pleaded to the public to reconsider their plan to visit the old tradition, especially for the year 2020.